1967
DOI: 10.1128/jb.93.3.996-1000.1967
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Characterization of the Genus Brucella VI. Growth Stimulation by i -Erythritol Compared with Strain Virulence for Guinea Pigs

Abstract: Strains of Brucella abortus isolated 20 to 38 years ago and strains recently isolated were assessed for their virulence to guinea pigs and for their ability to grow in halfstrength Tryptose Broth with and without i-erythritol. The recently isolated strains were virulent and i-erythritol enhanced their growth. The aged strains were avirulent and grew equally well in both media. Three of the recently isolated strains were subcultured serially every 24 hr alternately on Tryptose Agar slants and in halfstrength Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

1968
1968
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 4 publications
0
12
0
1
Order By: Relevance
“…Experimental evidence strongly suggests that the differential virulence of the B. abortus dhbC mutant in mice and ruminants stems from the inability of this mutant to replicate efficiently in the presence of the four-carbon sugar alcohol erythritol when faced with iron limitation (Bellaire et al, 2003b). Erythritol is the favoured carbon source for B. abortus strains (Meyer, 1967;Sperry and Robertson, 1975), and ruminant placental trophoblasts begin producing copious quantities of this compound at the onset of the last trimester of pregnancy (Smith et al, 1961;Enright, 1990). This is the same time at which pregnant ruminants are most susceptible to infection by the brucellae.…”
Section: 3-dhba Production and Iron Acquisition In The Reproductivementioning
confidence: 99%
“…Experimental evidence strongly suggests that the differential virulence of the B. abortus dhbC mutant in mice and ruminants stems from the inability of this mutant to replicate efficiently in the presence of the four-carbon sugar alcohol erythritol when faced with iron limitation (Bellaire et al, 2003b). Erythritol is the favoured carbon source for B. abortus strains (Meyer, 1967;Sperry and Robertson, 1975), and ruminant placental trophoblasts begin producing copious quantities of this compound at the onset of the last trimester of pregnancy (Smith et al, 1961;Enright, 1990). This is the same time at which pregnant ruminants are most susceptible to infection by the brucellae.…”
Section: 3-dhba Production and Iron Acquisition In The Reproductivementioning
confidence: 99%
“…At that time these investigators suggested that the increased virulence of in vivo-grown organisms in a guinea pig model was due to a cell wall component distinct from the major antigenic lipopolysaccharide. In addition, B. abortus has been shown to preferentially utilize the four-carbon aliphatic alcohol erythritol, which is present at high concentrations in infected bovine tissues (19). Our goal was to determine any changes which potentially occur in B. abortus as a result of changing environmental conditions during the course of infection and which play a role in intracellular survival and virulence.…”
mentioning
confidence: 99%
“…In contrast to domestic animals, the bacteria cause a chronic disease in man in which cells of the reticuloendothelial system are parasitized. It is significant that erythritol is present only in fetal fluids and tissues of animals which suffer acute infectious abortions; however, considerable controversy has been raised concerning possible relationship(s) between erythritol utilization and virulence (23,24). Infections with B. melitensis and B. suis have been enhanced by co-injection of erythritol (20).…”
mentioning
confidence: 99%
“…McCullough and Beal (22) studied the utilization of carbohydrates by 12 strains of Brucella and found that erythritol was the only sugar which supported growth of all strains. More recently, several hundred strains of Brucella were examined for ability to catabolize erythritol, and only the culture of B. abortus used for vaccine production in the United States was negative (18,23,24).Since animal tissues do not appear to catab-619 on August 1, 2020 by guest…”
mentioning
confidence: 99%